Intra Arterial Heparin Flushing Increases Manual Muscle Test – Medical Research Councils (MMT-MRC) Score in Chronic Ischemic Stroke Patient - Putranto, Terawan Agus; Yusuf, Irawan; Murtala, Bachtiar; Wijaya, Andi (BALI MEDICAL JOURNAL, 2016)
Background: Muscle strength impairment in stroke patient affect the patient daily life, especially when it occurs on the extremities muscles. Manual Muscle Testing (MMT) is an examination method to measure muscle strength using standardized scoring. Objective: To find possible improvement of Manual Muscle Test (MMT) Score after administration of Intra Arterial Heparin Flushing in chronic ischemic stroke patient. Method: This is an experimental study using pretest-posttest group design, with randomized controlled clinical trial, conducted among patients in Cerebrovascular Center Unit in Army Central Hospital Gatot Soebroto starting from February 2014. With 75 patients included in this study. The examination of muscle strength was done by trained physicians. The MMT score were taken before and after the IAHF procedure is conducted. Results: This study found higher score of MMTMRC scoring system on chronic stroke patient with IAHF procedure (mean MMT-MRC Score = 6,05 point. With p